NUTMEG PICKING ROVER - Paulose, Albin; Joy, Richard; Sonika P S,; Devassy, Mrs Binet Rose (International Journal of Psychosocial Rehabilitation, 2020)
Nutmeg farming is one of the leading economies in Kerala. Harvesting nutmeg manually is tiresome and time-consuming process. Around 40 % of the labour goes into the collection of the nutmeg from the farms. The time and effort used for the harvesting of the nut can be greatly reduced by automating the process. Currently there are no device in the market to pick and harvest this kind of fruits and nuts. The use of automated machines is no longer limited to industrial environments. Also for the outdoor activities robotic systems are increasingly combined with new technologies to automate the labour intensive works. Our project concentrates on automating the entire harvesting process from collecting the nuts from the farm to keeping it in the storeroom. The machine collects the nuts and once the onboard container is full, the machine goes to the store to empty the container. The machine also charges voluntarily once the charge goes below a threshold by coming to the charging dock. All this is done by GPS mapping and image processing.